The growing interest for joint interpretations of investment treaties by state parties - Charles-Emmanuel Côté; Shotaro Hamamoto; Marcin J. Menkes; Xu Qian (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
There is a growing interest for joint interpretations (JIs) of international investment agreements (IIAs) by state parties. Correct legal characterization of the vast array of JIs is critical to their proper use by tribunals in interpreting IIAs. This Perspective argues that a streamlined approach to JIs will encourage states to use them.
Keywords: 330